Štíhlá výroba a její implementace - Kuthanová, Dominika (Vysoké učení technické v Brně. Fakulta podnikatelská, 2019)
Diplomová práce se zabývá problematikou štíhlé výroby ve vybrané společnosti. Analytická část zahrnuje představení společnosti a analýzu současného stavu s využitím nástrojů štíhlé výroby k optimalizaci materiálových toků. Práce je rozdělena do čtyř částí. První část popisuje cíle a metodiku, následují teoretická východiska práce a analýza současného stavu společnosti. Závěrečná část zahrnuje návrhy možných řešení vedoucích k eliminaci či zlepšení zjištěných problémů.

The diploma thesis deals with the problematics of lean production in a selected company. The analytical part includes the introduction of the company and the analysis of the current state with using lean manufacturing tools to optimize material flows. The thesis is divided into four parts. The first part describes the objectives and methodology, followed by the theoretical basis of the work and analysis of the current state of the company. The final part includes suggestions of possible solutions leading to elimination or improvement of identified problems.
Lean Manufacturing and its Implementation
Keywords: Štíhlá výroba; Mapa toku hodnot; ABC-XYZ analýza; Zlepšování procesů; Lean manufacturing; Value stream map; ABC-XYZ analysis; Process improvement